Auditor's Guide to M&A Scandals. Issue 4 (17th April 2013) - Shapiro, David
Abstract Companies have grown ever larger by regularly consolidating and acquiring other businesses, in an effort to compete globally. The author of this article, a veteran financial investigator, has worked for the FBI, a New Jersey county prosecutor's office, and others. He says that the countervailing force of antitrust enforcement too often plays second fiddle or is passive in the face of freewheeling, deregulated merger and acquisition (M&A) activity. In this article, he reveals some of the detrimental by‐products of M&A, including the increased risk of corruption. He also discusses the auditor's role in detecting—and preventing—these adverse M&A by‐products and risks. © 2013 Wiley Periodicals, Inc.